Growth Performance and Economic Evaluation of Acacia Mangium Willd. Planted at Different Spacings - Phouthavong, Sinhsamouth (1998)
Acacia mangium Willd. is one of the fast-growing timber species planted widely in Malaysia to overcome the expected timber deficit for the wood based industries. However, comprehensive studies on planting distance and economic evaluation of A. mangium planted at different spacings have not been well documented. A trial plot at Universiti Putra Malaysia Serdang, Malaysia planted with A. mangium at five different spacings; namely S1 (2.0 m x 2.0 m), S2 (2.5 m x 2.5 m), S3 (3.0 m x 3.0 m), S4 (3.5 m x 3.5 m) and S5 (4.0 m x 4.0 m) was investigated to determine specifically the survival percentage, total height, diameter at breast height, volume, growth and yield prediction up to 15 years, soil physical and chemical properties, and relationship between tree growth and soil properties. Economic analysis of each spacing (with project) vs. 3.0 m x 3.7 m spacing (without project) was also conducted. The experimental results indicate that spacing 82 achieved the best survival percentage (81 %) and the best mean total height growth (20.40 m). The biggest mean diameter at breast height growth (21.46 cm) was recorded for spacing 85• The analysis of variance indicated that spacing does not affect total height growth, but affects diameter at breast height. The highest mean volume (0.407 m3) was found in spacing S5 and the highest wood volume per hectare (585.12 m3) was for spacing SI at 70 months old. The growth prediction using Gompertz model showed that spacing 82 recorded the highest mean total height value (24.77 m) and spacing S5 had the biggest mean diameter at breast height (26.20 cm). The highest predicted mean merchantable volume (0.581 m3) was for spacing 85. The yield prediction showed that spacing 81 produced the highest wood volume (211.44 m3) per hectare at year15. The analysis of variance showed that the soil chemical properties only differed significantly in carbon and iron. The correlation analysis showed that tree growth was not significantly correlated with most of the soil properties. The results of economic analysis indicated that spacing 81 was the most viable and profitable activities using IRR (14.01%). The sensitivity analysis showed that the changes in costs and benefits have low impact on the NPV, B/C ratio and IRR of 81. Therefore, 81 (2.0 m x 2.0 m) could be the most promising spacing in terms of wood production and economic returns.